Necessidades formativas dos professores de classes multisseriadas da educação do campo na Amazônia: apontamentos para uma proposta de formação continuada - Thomé, Sarah Elimery Sampaio (2022)
One of the main challenges imposed on rural education is the quality of teaching offered in the context of multigrade classes, which, on the other hand, is closely bonded to the educational training of teachers who have worked in this educational reality. With this regard, what moved this research was to think about the educational training of these professionals based on their needs. The general objective was to investigate the educational training needs of multigrade classes teachers in rural education – from early childhood education to the fifth year of elementary school –, aiming to present notes of a proposal for continuing education. Being a qualitative approach research, the data collection was carried out through a questionnaire and semi-structured individual interview, applied to six teachers working in the public schools in the rural region of Manaus, state of Amazonas. The data production procedure considered two axes: characterization and professional performance of the participants. Data were produced through the questionnaire for the first axis and interviews were carried out for the second axis. For the analysis procedure, the data produced were treated based on the assumptions of content analysis. As a result, this study revealed that teachers feel challenged when they face the reality of multigrade classes, that is, the heterogeneity of the class and the context of the students. The teachers' hearing about their training needs contributed not only to the development of notes aimed at a proposal for continuing education, based on the appreciation of culture and the specificities of individuals and the contexts of rural schools, but also for the recognition of the relevance of educational training processes based on the needs of teachers, it means, considering the real working situations context which are so peculiar to these professionals